The Effects of Trade Openness on Regional Inequality in South Korea - Soojeong Heo; Jinhwan Oh (European Regional Science Association (ERSA), 2015)
This paper is to analyze the effect of trade openness on regional inequality of South Korea. Trade has been the driving force of Koreas economic growth since the 1960s and it still expands its trade openness through active participation on bilateral and multilateral free trade agreements. In regard to this, this study measures the impact of Koreas trade openness on the countrys regional inequality using several sub-national panel dataset covering between 2003 and 2012. All data set for the 16 regional units (nine provinces and seven metropolitan cities) are collected from archival materials in Korean Statistical Information Service (KOSIS). The dependent variable is the growth rate of GDP per capita from.2000 to 2012, while the explanatory variables include human capital, trade openness, infrastructure, and per capita income. More specifically, human capital is measured by the number of people who have achieved university level education and infrastructure is measured by either road density or per capita number of cars, depending on data availability. Unlike other studies, this paper finds that trade openness contributes to higher level of economic growth on the regions with lower levels of education, implying that trade openness leads reducing regional inequality of Korea. In addition, trade benefits the areas with relatively lower per capita income, which also supports the claim that trade contributes to narrowing the regional income discrepancies. However, a seemingly contradictory finding has been made; more trade openness benefits regions which have rich infrastructure, thereby leading more regional inequality. We argue that the former two effects exceed the latter, thereby leading concluding that trade openness has been playing a positive role in reducing the countrys regional income gap.
Keywords: R11; R12; R58; 330; Regional Inequality; Trade; Openness; Per capita income; Human Capital; Infra